1984
DOI: 10.1128/aem.47.5.1084-1089.1984
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid and lactate catabolism in trimethylamine oxide respiration of Alteromonas putrefaciens NCMB 1735

Abstract: The nonfermentative Alteromonas putrefaciens NCMB 1735 grew anaerobically in defined media with trimethylamine oxide as external electron acceptor. All amino acids tested, except taurine and those with a cyclic or aromatic side chain, were utilized during trimethylamine oxide-dependent anaerobic growth. Lactate, serine, and cysteine (which are easily converted to pyruvate) and glutamate and aspartate (which are easily converted to tricarboxylic acid cycle intermediates) were metabolized at the fastest rate. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
2

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 25 publications
4
21
0
2
Order By: Relevance
“…Bacterial culture medium and growth conditions. To determine the Na+ requirement of the organism, medium C, de-scribed previously (20), was used with the following modifications. NaCl (0.1 M) was included or omitted as indicated below.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial culture medium and growth conditions. To determine the Na+ requirement of the organism, medium C, de-scribed previously (20), was used with the following modifications. NaCl (0.1 M) was included or omitted as indicated below.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have explicitly examined individual amino acids as potential electron donors for anaerobic respiration. Serine, cysteine, glutamate, and aspartate are effective electron donors for anaerobic respiration by Alteromonas (Shewanllla) putrefaciens NCMB 1735 using trimethylamine oxide as the terminal electron acceptor [80]. Geovibrio ferrireducens can grow by coupling the oxidation of proline to the reduction of Fe(III) [6].…”
Section: Electron Donor Utilization and Dissimilatory Iron(iii) Reducmentioning
confidence: 99%
“…TMA is typically present during fish spoilage. Stenberg et al (1984) and Ringo et al (1984) have also demonstrated the importance of the culture conditions and of the composition of the medium (NaC1, serine, L-cysteine, formate, lactate, glutamate, aspartate) for the development of Shewanella putrefaciens.…”
mentioning
confidence: 99%